2014
DOI: 10.1002/anie.201409976
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regio‐ and Enantioselective Synthesis of N‐Substituted 2‐Pyridones: Iridium‐Catalyzed Intermolecular Asymmetric Allylic Amination

Abstract: The first iridium-catalyzed intermolecular asymmetric allylic amination reaction with 2-hydroxypyridines has been developed, thus providing a highly efficient synthesis of enantioenriched N-substituted 2-pyridone derivatives from readily available starting materials. This protocol features a good tolerance of functional groups in both the allylic carbonates and 2-hydroxypyridines, thereby delivering multifunctionalized heterocyclic products with up to 98% yield and 99% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 73 publications
(25 reference statements)
1
26
0
Order By: Relevance
“…As an extension of our previous works on Ir-catalyzed asymmetric allylic substitution reactions with nitrogen-containing aromatic rings, we recently disclosed a highly regio-and enantioselective synthesis of chiral N-substituted 2-pyridones via Ir-catalyzed intermolecular asymmetric allylic amination (Scheme 14). 47 The designed reaction involved 2-hydroxypyridine 57 as the nucleophile. Tautomeric equilibrium of 57 between its 2-hydroxypyridine form and 2-pyridone form allows facile N-attack on the p-allyliridium electrophile.…”
Section: Scheme 8 Ir-catalyzed Asymmetric Allylic Dearomatization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…As an extension of our previous works on Ir-catalyzed asymmetric allylic substitution reactions with nitrogen-containing aromatic rings, we recently disclosed a highly regio-and enantioselective synthesis of chiral N-substituted 2-pyridones via Ir-catalyzed intermolecular asymmetric allylic amination (Scheme 14). 47 The designed reaction involved 2-hydroxypyridine 57 as the nucleophile. Tautomeric equilibrium of 57 between its 2-hydroxypyridine form and 2-pyridone form allows facile N-attack on the p-allyliridium electrophile.…”
Section: Scheme 8 Ir-catalyzed Asymmetric Allylic Dearomatization Ofmentioning
confidence: 99%
“…Ir-Catalyzed Asymmetric N-allylation of 2-HydroxypyridineOriginally reported by the You group 47. Scheme 15.…”
mentioning
confidence: 98%
“…Electron‐neutral pyridone could also react smoothly to give the corresponding N‐allylated product with high ee ( 11 ad ). The absolute configuration was assigned to be S by comparison with literature data . Then we examined the scope of racemic allylic carbonates, especially those with small alkyl substituents, which are not easily available for the corresponding allene counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, methods for the efficient synthesis of new derivatives of these compounds have thus attracted the great interest of synthetic and medicinal chemists. However, a literature survey showed that efficient, direct approaches to the selective synthesis of N -alkylated 2-pyridone derivatives are much less well explored, as known methods generally suffer from certain drawbacks such as the lack of generality or selectivity, poor yields, the use of expensive transition-metal catalysts and/or a competitive process between N - and O -alkylation (poor chemoselectivity) [ 34 , 35 ]. Therefore, the development of novel straightforward approaches to densely substituted N -alkylated 2-pyridones still remains as a hot research topic.…”
Section: Introductionmentioning
confidence: 99%